2019
DOI: 10.1073/pnas.1900390116
|View full text |Cite
|
Sign up to set email alerts
|

Reduced default mode network functional connectivity in patients with recurrent major depressive disorder

Abstract: Major depressive disorder (MDD) is common and disabling, but its neuropathophysiology remains unclear. Most studies of functional brain networks in MDD have had limited statistical power and data analysis approaches have varied widely. The REST-meta-MDD Project of resting-state fMRI (R-fMRI) addresses these issues. Twenty-five research groups in China established the REST-meta-MDD Consortium by contributing R-fMRI data from 1,300 patients with MDD and 1,128 normal controls (NCs). Data were preprocessed locally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
380
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 568 publications
(459 citation statements)
references
References 40 publications
34
380
7
Order By: Relevance
“…All the images were preprocessed via a MATLAB toolbox, Data Processing Assistant for RS-fMRI (DPARSF) (Yan and Zang, 2010) which was based on Statistical Parametric Mapping (SPM8) 2 and RS-fMRI Data Processing Toolkit (REST) (Song et al, 2011). The first 10 time points (20 s) were discarded because the subject took time to adapt to the scanning noise and additionally for the scanner to calibrate (Zang et al, 2004;Wang et al, 2017;Yan et al, 2019). Given that there were only 170 time points in NYU data, we retained 170 time points for PKU1, PKU2, and PKU3.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…All the images were preprocessed via a MATLAB toolbox, Data Processing Assistant for RS-fMRI (DPARSF) (Yan and Zang, 2010) which was based on Statistical Parametric Mapping (SPM8) 2 and RS-fMRI Data Processing Toolkit (REST) (Song et al, 2011). The first 10 time points (20 s) were discarded because the subject took time to adapt to the scanning noise and additionally for the scanner to calibrate (Zang et al, 2004;Wang et al, 2017;Yan et al, 2019). Given that there were only 170 time points in NYU data, we retained 170 time points for PKU1, PKU2, and PKU3.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Supporting the relevance of brain connectivity in mood disorders, resting-state fMRI studies have reported aberrant connectivity within the default mode network (DMN) in patients with depression compared to healthy controls (Kaiser, Andrews-Hanna, Wager, & Pizzagalli, 2015;Mulders, van Eijndhoven, Schene, Beckmann, & Tendolkar, 2015;Yan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas these previous studies provided informative regional evidence, our results provided an overall network-wise interaction pattern. Critically, our primary finding adds to the recent challenge to the prevailing notion that rumination causes the abnormally enhanced within DMN-FCs in MDD patients (39), indicating rumination's DMN neural underpinnings are more nuanced than previous hypothesis have predicted.…”
Section: Discussionmentioning
confidence: 53%